PENGARUH KUALITAS SUMBER DAYA MANUSIA, KOMITMEN ORGANISASI, BUDAYA ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA ORGANISASI SATUAN KERJA PERANGKAT DAERAH (Studi Empiris Pada SKPD Kabupaten Kuantan Singingi) - Novita Indriana; Amries Rusli Tanjung; Azhari S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the effect of the quality of human resources, organizational commitment, organizational culture, and work motivation on the performance of organizations in the District Government of Kuantan Singingi. the population in this research is all regional work units kuantan singingi regency. The sample in the researth is regional work units kuantan singingi regency with 75 respondents, including the head o regional work units (SKPD), SKPD secretary, and head of local goverment throughout SKPD kuantan singingi regency. Data collection technique in this research is from questionnaires, while the data analysis tehnique which was used is multiple linear regresion analysis the processed using SPSS aid. The results showed thet the quality of human resources, organizational commitment, organizational culture, and work motivation significant effect on the performance of organizzations with significant <0,005. The calculation result obtainable value R 2 as big as 0.746. this shows that quality of human resources, organizational commitment, organizational culture, and work motivation may explain the variable of organization performance 74,6%.While the rest 25,4%influenced by variables that are not observed in this research model.Keywords: Quality Of Human Resources, Organiational Commitment, Organiational Culture, Work Motivation, Performance of Organization